Предмет: Математика,
автор: Паупаучика
решите уравнение f'(x)=0: a) f(x)=x³+3+3x²+3x+1; b) f(x)=x³-6x²+12x-1
Ответы
Автор ответа:
0
a)
f'(x) = 3x²+6x+3
3x²+6x+3 = 0 ÷3
x²+2x+1 = 0
(x+1)² = 0
x+1 = 0
x = -1
b)
f'(x) = 3x²-12x+12
3x²-12x+12 = 0 ÷3
x²-4x+4 = 0
(x-2)² = 0
x-2 = 0
x = 2
f'(x) = 3x²+6x+3
3x²+6x+3 = 0 ÷3
x²+2x+1 = 0
(x+1)² = 0
x+1 = 0
x = -1
b)
f'(x) = 3x²-12x+12
3x²-12x+12 = 0 ÷3
x²-4x+4 = 0
(x-2)² = 0
x-2 = 0
x = 2
Автор ответа:
0
а как решить через дискрименант?
Автор ответа:
0
Здесь он не нужен.
Автор ответа:
0
А вообще по формулам
Автор ответа:
0
D = b^2-4*a*c
Автор ответа:
0
cnacubo
Похожие вопросы
Предмет: Биология,
автор: nuykintatiana
Предмет: Французский язык,
автор: ariana4010
Предмет: Химия,
автор: Аноним
Предмет: Литература,
автор: Аноним